Factors Inﬂuencing the Proﬁtability of Listed Indonesian Commercial Banks Before and During Financial Global Crisis - Agustini, Menur; Viverita, Viverita (UI Scholars Hub, 2012)
As a country with bank-based economy, stability and soundness of its banking industry are cru-cial matters for Indonesia especially in dealing with the crisis period, such as ﬁnancial global crisis which occurred in 2008. Considering the crucial impact of the crisis, this study aims to examine determinants of bank proﬁtability (as the measurement of stability and soundness of banking industry) before and during the crisis period. Using the Generalized Method of Moment (GMM), this study analyzes the proﬁtability of listed commercial banks using unbalanced panel data over the period of 2002-2009. To investigate the impact of recent ﬁnancial global crisis, this study uses time dummy variable to separate the pre-crisis period (2002-2006) and during the crisis period (2007-2009). Findings of this study show that in the pre-crisis period, bank-speciﬁc factors i.e. lagged proﬁtability, bank size, bank capitalization, and diversiﬁcation and external factors which are inﬂation and stock market-based ﬁnancial development statistically and signiﬁcantly affect bank's proﬁtability. Further-more, the crisis is proven to have signiﬁcant impact on the effect of inﬂation and stock market-based ﬁnancial development toward bank proﬁtability. Whereas, through the general model which is not separate the pre and during crisis periods, this study shows that bank-speciﬁc factors such as lagged proﬁtability, bank size, and bank capitalization are proven to have signiﬁcant effects on bank proﬁt-ability while external factors that also have effects are bank-based ﬁnancial development and bank concentration.